The Legal Protection of "Strīdhana" and the Evolution of Hindu Succession Laws: A Gendered Perspective - Correndo, Chiara (Dopo di noi, 2025)
The contribution aims at developing an analysis of women’s property rights within the context of Hindu classical, postclassical and contemporary law investigating how the legal discourse contributed to shape the gendered subjectivity of women contributing to their further inner layering. In particular, this article will take into account the provisions related to women’s property rights, through the analytical lenses of "strīdhana" and succession, shedding light on the layered role of propertied women within the Hindu and Indian social contexts.